Exosomes in the Field of Neuroscience: A Scientometric Study and Visualization Analysis - Long, Junzi; Zhang, Yasu; Liu, Xiaomin; Pan, Mengyang; Gao, Qian (Frontiers in Neurology, 2022)
As Exosomes have received great attention for their diagnostic, therapeutic and prognostic roles in the field of neuroscience over the past decade. This scientometric study aimed to quantitatively and qualitatively evaluate knowledge structure, hot topics, and research trends of studies about exosomes in the field of neuroscience using visualization tools. Web of Science Core collection databases were searched for relevant publications between 2005 and 2021. The Carrot2 online system, BICOMB, gCLUTO and Ucinet softwares were utilized for key word analysis, and co-citation analyses were conducted in Citespace and VOSviewer. Altogether, 21 high-frequency key words were collected from 856 included articles, and 5 clusters were identified through biclustering analyses. The strategic diagram and social network analysis further determined research hotspots and trends. Co-citation analysis results showed that work by Emmanouilidou E et al. (2010) represented a milestone in this field, and study by Fiandaca MS et al. (2015) was crucial in the development of researches on exosomes in Alzheimer's disease. Moreover, the important sources that had contributed to the development of this field were identified. Our findings suggested that Alzheimer's disease-related researches remained a hot topic in this field till now, but recent researchers had extended the scope to more cognitive impairments. Importantly, researches related to exosomes in multiple sclerosis and Parkinson's disease were promising. While exosomes in acute central nerve system injury had not been sufficiently investigated, with continuous improvement in exosome-based delivery technology, this subject might make a breakthrough in terms of therapeutic innovations.